108k views
0 votes
Sum of 4x^3+6x^2+2x^2-3 and 3x^3+3x^2-5x-5 is

User Tyga
by
5.6k points

1 Answer

3 votes

9514 1404 393

Answer:

7x^3 +11x^2 -5x -8

Explanation:

Combine like terms.

(4x^3+6x^2+2x^2-3) + (3x^3+3x^2-5x-5)

= (4 +3)x^3 +(6 +2 +3)x^2 +(-5)x + (-3 -5)

= 7x^3 +11x^2 -5x -8

_____

Noting that the first expression contains two x^2 terms, we wonder if you actually want the sum ...

(4x^3+6x^2+2x-3) + (3x^3+3x^2-5x-5)

= (4 +3)x^3 +(6 +3)x^2 +(2 -5)x +(-3 -5)

= 7x^3 +9x^2 -3x -8

User Clebert Suconic
by
4.7k points